Inflammatory Cytokines and SIRT1 Levels in Subcutaneous Abdominal Fat: Relationship With Cardiac Performance in Overweight Pre-diabetics Patients - Sardu, Celestino; Pieretti, Gorizio; D'Onofrio, Nunzia; Ciccarelli, Feliciano; Paolisso, Pasquale; Passavanti, Maria B.; Marfella, Raffaele; Cioffi, Michele; Mone, Pasquale; Dalise, Anna M.; Ferraraccio, Franca; Panarese, Iacopo; et al. (Frontiers in Physiology, 2018)
Objectives: in obese patients the superficial adipose tissue expresses cytokines, and sirtuins, that may affect myocardial function. In this study we investigated the effect of metformin therapy plus hypocaloric diet on inflammatory pattern and cardiac performance (MPI) in pre-diabetics obese. Materials and methods: 58 obese patients enrolled for abdominoplastic surgery were divided in pre-diabetics and normo-glycemics. Pre-diabetics were randomly assigned to metformin therapy plus hypocaloric diet (group 1, n 20) or to hypocaloric therapy alone (group 2, n20). Normo-glycemics were assigned to hypocaloric diet. Results: At 12 months of follow up, metformin therapy induced in prediabetics (group 1) a significant reduction of glucose, HOMA-IR, and inflammatory markers as CRP (1.04± 0.48 vs. 0.49± 0.02 mmol/L, p value <0.05), IL6 (4.22±0.45 vs. 3.33±0.34 pg/ml, p value <0.05), TNFα (6.95±0.59 vs. 5.15±0.44 pg/ml, p value <0.05), and Nitrotyrosine (5,214±0,702 vs. 2,151±0,351 nmol/l, p value <0.05). This was associated to a significant reduction of Intima-media tickness (1.01±0.15 vs. 0.86±0.15 mm, p value<0.05), Septum (14±2.5 vs. 10.5±2 mm, p value<0.05), Posterior wall (11±1.5 vs. 8±1mm, p value <0.05), LV mass (192.5±49.5 vs. 133.2±37.6 g, p value <0.05) and of MPI (0.58±0.03 vs. 0.38±0.02, p value <0.05). At 12 months of follow up, group 2 experienced only a reduction of cholesterol (4.15±0.94 vs. 4.51±0.88 mmol/L, p value <0.05) and triglycerides (1.71±1.18 vs. 1.83±0.54 mmol/L, p value <0.05).At 12 months of follow up, group 3 experienced a significant reduction of inflammatory markers, and of echographic parameters, associated to amelioration of myocardial performance.To date, IL6 expression was related to higher values of left ventricle mass (R value 0.272, p value 0.039), and to higher IMT (R value 0.272, p value 0.039), such as observed for CRP (R value 0.308, p value 0.021), for glucose blood values (R value 0.449, p value 0.001), and for HOMA-IR (R value 0.366, p value 0.005). An inverse correlation was found between subcutaneous fat expression of SIRT1 and myocardial performance index (R value -0.236, p value 0.002). Conclusion: in pre-diabetics obese patients metformin therapy may reduce inflammation and oxidative stress, and this may be associated to the amelioration of the cardiac performance.